Modelling Of Solar Irradiance For Sizing Global And Perpetual Solar-Powered Unmanned Aerial Vehicle (Uav) - Masral, Muhammad Hazim (2016)
There are various applications of small unmanned aerial vehicle for both military and civil aviation in recent years. The opportunity to enhance of solar-powered UAV capabilities to operate as pseudolite satellite enables all countries around the world an endless possibility of their own technology. However, weight and power restriction are always the main cause which limits UAV to operate as pseudolite satellite. The aim of this work is to bridge the knowledge gap in the area of perpetual flight across regions around the world for a yearlong operation. Through this study, focus has been given 1) to study both local and global solar modelling and 2) how these solar data may enable the possibilities of developing a UAV design capable of global operation. In this study, for local solar modelling, 14 variant proposed models are studied with its relevant parameters using the regression technique. Then, as for global solar modelling, the theoretical approach has been used to study twelve cities spreading all over the world. The performance of each proposed solar model in estimating the solar irradiance (SI) for Malaysia is analysed based on its Root Mean Square Error (RMSE), Coefficient of Determination (R2) and Mean Bias Error (MBE). Finally, the analyses carried out to understand the feasibility of a perpetual solar-powered UAV operated around the world have been simulated. Here, the two modes of study include 1) AUAV; the yearly average solar data simulation to design solar-powered UAV suitable for operation at each city, and 2) GUAV; a single optimized solar-powered UAV design that is capable for operation in all cities investigated in this work.Proposed Model (PM) 12 had been recommended as solar estimation model for Malaysia, the result showed that the RMSE for the model is 0.856%, MBE0.282% and R2 is 0.988. An optimum design specification for Global UAV (GUAV) successfully to simulate perpetual flight for whole year with specification of Maximum Take-Off Weight (MTOW) 0.5057 kg, Wingspan (S) 2.03 m and Solar Wing Area Ratio (SWAR) 40%. Based on Global SI data year 2013, we able to estimate the best diffuse factor value for Malaysia, which is 60.8% by using interpolation method. Keywords-component; global solar irradiance; meteorology station data; clouds cover; temperature; wind speed; gust speed; rain precipitate; relative humidity, pressure, regression method; UAV; pseudolite; weight; sizing configuration